Plan de Marketing para la microempresa “Cobro Gestión y Abogados R&B Cia Ltda” de la ciudad de Loja, en el periodo 2021-2022. - Cuenca Herrera, Victor Fabricio (2023)
This investigation paperwork aims to develop a "MARKETING STRATEGIC PLAN FOR THE COMPANY COBRO GESTIÓN ABOGADOS R&B LIMITED COMPANY," located in the City of Loja, to develop strategies to increase the client portfolio through a situational analysis. For the implementation of the marketing plan, we analyzed the diagnosis of internal and external factors; in the internal evaluation, we conducted an interview with the manager of the company and used the direct observation form, supporting the present research work; we defined the strengths and weaknesses of the company, we contrasted these in the EFI Matrix, with a score of 2,60 indicating that the fortresses predominate over the shortcomings. In the external diagnosis, we applied surveys to the company's clients. In addition, a PEST analysis allowed for determining the impact of political, economic, social and technological and factors. And we also performed a study of Porter's five forces. With the information contrasted in this diagnosis, we made the SWOT Matrix. Based on the results obtained, we proceeded to propose strategies for the marketing plan proposal; we formulated six strategic objectives to position the company in the market, and for each aim, we considered the: objective, goal, strategy, policies, activities, tactics, responsible parties, and budget which total cost is the estimated amount of $1.220,80. Once we completed the research work, we established the respective conclusions and appropriate recommendations that the company should take into account to achieve its objectives and perform better in the market.